Analisis Usaha Budidaya Sapi Potong (Studi Kasus: Desa Pertambatan, Dolok Masihul Kabupaten Serdang Bedagai) (Universitas Medan Area, 2020)
North Sumatra Province is one of the provinces with the largest coffee production in Indonesia. The type coffee produced in North Sumatra province are coffee arabica and robusta. North Sumatera Province had no doubt in exporting palm oil commodity, and rubber to many countries. North Sumatra Province can not just rely on both of that commodities and therefore it is necessary to other alternatives such as coffee. Volume and value of coffee exports fluctuated reflecting the competitiveness of North Sumatra Province coffee needs to be improved. The aim of this research to analyze the comparative advantage, a tendency to be exporter or importer of coffee and coffee export projection of North Sumatra Province. The method used is the Revealed Comparative Advantage (RCA), Trade Specialization Index (TSI) and Trend. The result showed that North Sumatera Province coffee has a competitiveness and as coffee exporter and the projection of coffee export was positive for the next 5 years.